Measuring Systemic Risk in Vietnam’s Banking System (International Journal of Scientific Research and Management (IJSRM), 2025)
In the context of globalization and increasing economic integration, systemic risk in the banking sector has emerged as a critical threat to the stability of modern economies, particularly in emerging markets like Vietnam. This study focuses on applying the CoVaR (Conditional Value-at-Risk) index to measure systemic risk in Vietnam’s commercial banking system, a method chosen for its ability to capture spillover effects and market volatility during periods of financial instability. Utilizing daily stock price data from 18 listed commercial banks between 2015 and 2024, the research provides new empirical evidence on their systemic risk contributions. The findings reveal distinct phases of systemic risk, with a notable increase during the 2022 period, and identify specific institutions with higher contributions to systemic risk. From a theoretical perspective, this study contributes to the academic literature by providing empirical evidence on systemic risk using CoVaR in an emerging market context. From a practical standpoint, it offers evidence-based policy recommendations to enhance systemic risk monitoring and mitigation, particularly for identifying systemically important institutions, thereby supporting targeted supervision and the establishment of appropriate capital and liquidity requirements. These findings aim to bridge the gap between theory and practice in systemic risk management in Vietnam and provide a foundation for regulators to develop more effective control measures.